AKAR PEMBAHARUAN ISLAM DI INDONESIA ABDR AL-RAUF AL-SINKILI - Zaenuddin, Zaenuddin (Kopertais Wilayah X Jawa Tengah, 2013)
AbstractAbd Al-Rauf Al-Sinkili was an Islamic leader who had expertise in combining two disciplines, that are tashawwuf and fiqh, in a systematic way. According to Al-Sinkili, the two discipines must be placed in harmony so that they do not come to surface as contradictory things in such ways and become overlap in the end. Tashawwuf (which involves spiritual matters), is a complementary science to Fiqh (which involves physical matters) for MoslemsÂ to implement a proper religious life in order to have the mercy from Allah swt.A piece of writing that soon became a master piece by Al-Sinkili was entitledÂ â€œMir'at Al-Thulab fi Tahsil Ma'rifat al-Ahkam al-Syariâ€™ah li al-Malik al-Wahhabâ€. The piece was supposed to be a primary reference in Islamic Law for those who follow Syafiâ€™ism. Â While his writing concerning with tashawwuf was entitled â€œDaqoiq al-Hurufâ€ (means the mistery of syllables) was the book on mysticism that explained about the misteries of symbolical aspects on syllables in connections with human interactions with the others, as well as with Allah swt.To some extent, the expertise shown by Al-Sinkili had weakened the accusations made by contemporary scholars toward ulamas in this archipelago for being occupaid by such a discourse in Islamic thought, and set aside the real global challenges. Â This accusation is, of course, irrelevant for the time being as since XVII century there had been a dynamic development on Islamic thoughts made by Javanese ulamas. This was, at least evidenced by the emergence of modern thought about some possibilities for women to be a leader in the country.Key words: al-Sinkili, harmony, tashawwuf, fiqh.